“Efecto de sobra y frecuencia de riesgo en la etapa de aclimatación de plantas clonadas de café (coffea arabica L.) variedad caturra en fase de vivero, morales-San Martín” - Abad Retete, Manuel (2015)
He coffee is the main product agricultural of export in the country, in the year 2013 the Peru exported 5'600, 000 quintals (qq), generating an income of 1,400 million of dollars to the economy national. Our country is one of the leaders in the production of specialty coffees (product that distinguishes itself from the other cafés have better physical and organoleptic qualities), with a growing demand in the international market. (National Ministry of agriculture, 2013). In the high jungle of Peru this crop is an important source of employment, since it generates fifty thousand seven hundred million wages only in agricultural activity. Jobs for transportation and services, can exceed sixty thousand wages. Coffee is a culture that generates economy in a country, but growers have large losses in the production of seedlings produced from seeds when they are installed to final fields, so this research aims to optimize the proc...